THE EVALUATION OF 3176 UPPER GASTROINTESTINAL ENDOSCOPIC EXAMINATIONS - M. Kadir AKSÖZ; Z. Abidin ALTINAY; Belkıs ÜNSAL; Nafi YAZICIOĞLU; Bülent KARA; Himmet KARACA; Sadun KOŞAY (Turkish Journal of Gastroenterology, 2020)
-